Prospects and Challenges of Shar’i Insurance in Efforts to Compensate Victimsof Natrual Disaster in Indonesia - ellectrananda anugerah ash-shidiqqi; Aidul Fitiada Azhari; Kelik Wardiono; Wardah Yuspin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The presence of sharia insurance in Indonesia complements the presence of types of insurance in Indonesia. The existence of sharia insurance in an effort to compensate victims of natural disasters is very important because the existence of Muslims requires halal certainty from insurance, how it differs from conventional products, what are the prospects in Indonesia and what are the challenges faced. Qualitative descriptive method was chosen to describe the condition of Islamic insurance in Indonesia. The results of the study indicate that in the development of sharia insurance in an effort to compensate victims of natural disasters, there are prospects, obstacles and various supports needed for the development of sharia insurance in Indonesia, synergy between Ulama, government Umara in the form of regulation and supervision